English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

the equation is square root of (5x-3) = square root of (2x+3)

2006-09-24 15:34:58 · 7 answers · asked by Need Help 2 in Science & Mathematics Mathematics

7 answers

Ok, so 5x-3 must equal 2x+3. Can you solve it from there?

2006-09-24 15:36:50 · answer #1 · answered by Anonymous · 0 0

Square both sides to get
5x-3=2x+3
-2x -2x
3x-3=3
+3 +3
3x=6
/3 /3
1x=6/3
x=2

2006-09-24 22:39:41 · answer #2 · answered by Robert B 5 · 1 0

square both sides in order to eliminate the square root sign.
then equal the 2 equations and you`ll get as answer x=2

2006-09-25 08:21:47 · answer #3 · answered by sweetfloss8 2 · 0 0

x=2
(5*2)-3 = 7
(2*2)+3 = 7
square root of 7 = 2.65

2006-09-24 22:38:19 · answer #4 · answered by southernguy 2 · 1 0

Pa says that you dont need math only your two hands and a good rifle

2006-09-24 22:36:40 · answer #5 · answered by Anonymous · 0 0

Man, you're right. You do need help.

2006-09-24 22:36:31 · answer #6 · answered by applesherrytwist 2 · 0 0

southernguy is wrong

2006-09-24 22:47:07 · answer #7 · answered by saddlesore 3 · 0 0

fedest.com, questions and answers